Відображення середньополіської говірки в романі-гризайлі Миколи Закусила "Норинчанка і птах" - Громик, Юрій Васильович; Hromyk, Yurii V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проаналізовано специфіку відображення рис середньополіської говірки в романі-гризайлі Миколи Закусила «Норинчанка і птах», зокрема доречність запропонованих автором графічних та орфографічних новацій, послідовність відтворення діалектних особливостей, з’ясовано місце говіркових елементів у структурі художнього тексту.

The article provides comments on the specifics of presenting the middle-Polissian dialect in the new novel by Mykola Zakusylo. The emphasis is laid on the appropriateness of graphic and orthographic innovations. This study seeks out to identify the consistency of reproducing dialectal peculiarities and determines the place of dialectal elements in the structure of an artistic text. The author argues that the novel can be regarded as an interesting experiment on the use of dialect in the function of literary language. However Polissian colloquial language features, especially at the phonetic level, are reflected by M. Zakusylo inconsistently, since he accumulates elements from different dialects of the right-bank Polissia. The innovations at the level of graphics and spelling are critically analyzed and evaluated in the article. The author of the article claims that in the absence of punctuation marks and lack of clarity in the division of the text into sentences, graphic experiment makes an impression of artificiality, sometimes complicating perception and understanding of the content of the novel.
Reflection of Middle-Polissian Dialect in the Novel «Norynchanka and a Bird» by Mykola Zakusylo
Keywords: середньополіська говірка; діалектизм; художній текст; роман- гризайль; М. Закусило